PENGARUH PENGHINDARAN PAJAK, KEBIJAKAN DEVIDEN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PERENCANAAN PAJAK SEBAGAI VARIABEL PEMODERASI - Annisa Indah Lestari; Chaidir Djohar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine and provide empirical evidence regarding the effect of Tax Avoidance, Dividend Policy, and Company Growth on Firm Value with Tax Planning as a Moderating Variable. The value of the company. The population in this study are Food and Beverage companies listed on the IDX in 2017-2021. The number of samples used in this study were 10 companies obtained by purposive sampling method. The type of data used in this research is secondary data using quantitative methods. This research was processed using eviews 10 software. The results of this study are Tax Avoidance has no effect on Firm Value, Dividend Policy has an effect on Firm Value, Company Growth has no effect on Firm Value, Tax Avoidance, Dividend Policy, Company Growth has an effect simultaneously on Value Company, Tax Planning is able to moderate the effect of Tax Avoidance on Firm Value, Tax Planning is able to moderate the effect of Dividend Policy on Firm Value, Tax Planning is able to moderate the effect of Company Growth on Firm Value